Altitude training experience of Italian race walking coaches - La Torre, A.; Pugliese, L.; Capitanio, I.; Pavei, G. (Slovak Journal of Sport Science, 2017)
Altitude training is a common practice in endurance athletes. It is mainly used to obtain improvement in performance thanks to adaptation at both central (e.g. maximal oxygen uptake and haematological parameters) and peripheral level (e.g. mitochondrial efficiency and muscle buffering). In the literature has been reported that also race walkers underwent altitude training camp during annual training program, the methodologies involved were however different due to different aims, thus dissimilar results were found. The aim of this paper was to understand in which extent Italian race walkers coaches use altitude training. Four coaches were interviewed in order to obtain their experience about altitude training (camp numbers, altitude level, training methodologies, timing and goals). All coaches utilized live high-train high methods for law (in Italy artificial hypoxia is illegal) and logistics reasons. The altitude high was different with half using moderate altitude and others high altitude. All reported to use altitude training mainly for improving athletes' performance due to peripheral (moderate altitude) and central and peripheral (high altitude) enhancement. All coaches paid attention to acclimatisation period (both at altitude and back to sea level), which is subjective and altitude-experience dependent, however it lasts no longer than ten days. The training intensity was kept as close to sea level as possible by adopting interval and high-intensity training. Overall coaches' answers pointed out a great knowledge of the physiological and training basis of altitude training. The efficacy of any training for elite athletes is met only when an adequate stimulus is given to athletes, and also altitude training has to follow this rule. Along this line of thought coaches understand that only living high with some training volume cannot meet the efficacy criteria. Thus, let athletes train with an intensity as close to sea level as possible in order to give and higher stimulus and to gain more benefits when athletes will be back at sea level